The Effect of Emotional Intelligence on Academic Achievement at Khaira Ummah Islamic Junior High School In Padang - Syifaa, Syifaa; Hendri , Nofri (Green Publisher Indonesia, 2026)
Emotional intelligence plays a crucial role in how students manage academic pressure, build social relationships, and stay motivated during the learning process. However, many students still struggle with emotional regulation, which can negatively impact their academic achievement. The purpose of this study is to investigate experimentally how much emotional intelligence factors affect students' learning outcomes at Padang City's Khaira Ummah Islamic Junior High School. An associative design and quantitative methodology were employed. A structured questionnaire instrument was used to gather data from 92 respondents in order to quantify emotional intelligence profiles and document student academic grades. After confirming that the data satisfied the traditional assumptions (normality and linearity), a straightforward linear regression test was used to analyze the data. The results of the study show that emotional intelligence significantly improves student learning outcomes (Sig. 0.017 < 0.05). According to the coefficient of determination, emotional intelligence accounts for 24.8% of the diversity in learning outcomes, with other internal and external factors accounting for the remaining portion. The study's conclusions highlight how crucial it is to incorporate emotional learning into the educational process in order to enhance academic achievement in a comprehensive way